Early Intervention in Psychosis: Efficacy of the Screening Program - Razali, Salleh Mohd; Othman, Zahiruddin; Abidin, Zarina Zainal; Yassin, Mohd Azhar Mohd (Japan International Cultural Exchange Foundation, 2011)
Aims; To screen and detect individuals at ultra high risk (UHR) for psychosis and evaluate the efficacy of a screening program Methods: This is a two-stage study involving relatives of patients with schizophrenia. The first degree relatives were screened with the GHQ-12 and non-first degree relatives were additionally screened with the selfconstructed screening questionnaires (SQ). All the positive suhjects from the initial screening will he proceeded to the second stage screening. Results: Fifteen (13.5%) of 111 subjects were positive in the first stage. After the second stage screening, only 3 (2.7%) were positive (UHR suhject). Two (2.6%) cases were first degree relatives and the other one (3%) was non-first degree relatives. Although the majority of the positive suhjects in the initial screening were detected through the GHQ-12, only one of them was positive in the second stage. Conclusion: Screening of genetic risk relatives of schizophrenia is feasible. The detection rate of subject at UHR was much lower than expected, especially among first degree relatives. The higher detection rate among non-first degree relatives is contrihuted by the addition of the SQ. The GHQ-12 is not suitable for screening in early psychosis; it should he comhined with other screening instruments.